A 24 GHz wideband monostatic FMCW radar system based on a single-channel SiGe bipolar transceiver chip. Issue 3 (23rd April 2013) - Bredendiek, Christian; Pohl, Nils; Jaeschke, Timo; Thomas, Sven; Aufinger, Klaus; Bilgic, Attila
Abstract : In this paper a monostatic frequency-modulated continuous-wave (FMCW) radar system around a center frequency of 24 GHz with a wide tuning range of 8 GHz (≈33%) is presented. It is based on a fully integrated single-channel SiGe transceiver chip. The chip architecture consists of a fundamental VCO, a receive mixer, a divider chain, and coupling/matching networks. All circuits, except for the divider, are designed with the extensive use of on-chip monolithic integrated spiral inductors. The chip is fabricated in a SiGe bipolar production technology which offers an fT of 170 GHz and fmax of 250 GHz. The phase noise at 1 MHz offset is better than −100 dBc/Hz over the full-tuning range of 8 GHz and a phase noise of better than −111 dBc/Hz is achieved at 27 GHz. The peak output power of the chip is −1 dBm while the receive mixer offers a 1 dBm input referred compression point to keep it from being saturated. The chip has a power consumption of 245 mW and uses an area of 1.51 mm 2 . The FMCW radar system achieves a power consumption below 1.6 W. Owing to the high stability of the sensor, high accuracy mesaurements with a range error <±250 µm were achieved. The standard deviation between repeated measurements of the same target is 0.6 µm and the spatial resolution is 28 mm.